Pentecostais e Neopentecostais na Câmara Municipal de Curitiba (1989-2016): práticas e representações - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2017)
This research has as object the acting of pentecostals and neopentecostals politicians in the City Council of Curitiba in the years of 1989 to 2016. The objective is explain and comprehend the practices and representations of pentecostals and neopentecostals concerning public politics in a City Council. It uses as a theoretic and methodological scope ideas connected with New Cultural History, mostly the concepts of practices and representations. It dialogues also with the social fields theory of Pierre Bourdieu. The discussion dealing with the interactions, tensions, approximations and interferences between the religious and political fields inside an (pretence) laic State. Furthermore, the political representation of religious people in an laic ambient and discussion. Some historical sources are documentation constant in the legislative processes, journalistic materials, biographic books and interviews. The first chapter aims to contextualize the arrival and development of pentecostalism in Brazil and its relationship with the society. The second part analyses the performance of pentecostal and neopentecostal councilmen in the City Hall of Curitiba in the referred period.Finally, the third part analyses the performance of this actors in a specific subject: the discussion related to the gender thematic, mainly in what in his discourse became known as the Gender Ideology.
Keywords: Políticos pentecostais e neopentecostais; Câmara Municipal; Curitiba; Práticas e representações; Ideologia de gênero; Pentecostals and neopentecostals politicians; City council; Curitiba; Practices and representations; Gender ideology; CNPQ::CIENCIAS HUMANAS::HISTORIA